Biomechanical Strength of Retrograde Fixation in Proximal Third Scaphoid Fractures - Daly, Charles A. (Hand (N Y), 2018)
Background: Current techniques for fixation of proximal pole scaphoid fractures utilize antegrade fixation via a dorsal approach endangering the delicate vascular supply of the dorsal scaphoid. Volar and dorsal approaches demonstrate equivalent clinical outcomes in scaphoid wrist fractures, but no study has evaluated the biomechanical strength for fractures of the proximal pole. This study compares biomechanical strength of antegrade and retrograde fixation for fractures of the proximal pole of the scaphoid. Methods: A simulated proximal pole scaphoid fracture was produced in 22 matched cadaveric scaphoids, which were then assigned randomly to either antegrade or retrograde fixation with a cannulated headless compression screw. Cyclic loading and load to failure testing were performed and screw length, number of cycles, and maximum load sustained were recorded. Results: There were no significant differences in average screw length (25.5 mm vs 25.6 mm, P = .934), average number of cyclic loading cycles (3738 vs 3847, P = .552), average load to failure (348 N vs 371 N, P = .357), and number of catastrophic failures observed between the antegrade and retrograde fixation groups (3 in each). Practical equivalence between the 2 groups was calculated and the 2 groups were demonstrated to be practically equivalent (upper threshold P = .010). Conclusions: For this model of proximal pole scaphoid wrist fractures, antegrade and retrograde screw configuration have been proven to be equivalent in terms of biomechanical strength. With further clinical study, we hope surgeons will be able to make their decision for fixation technique based on approaches to bone grafting, concern for tenuous blood supply, and surgeon preference without fear of poor biomechanical properties.